Analisis Kontribusi dan Efektivitas Pendapatan Asli Daerah Kabupaten Manggarai Tahun 2017-2019 - Redemptus Ntangis Holymayor; Yulia Setyarini (Bulletin of Management and Business, 2022)
The Republic of Indonesia is the largest archipelagic country in the world, which consists of various provinces, cities and regencie. Based on Law Number 12 of 2008 concerning the Second Amendment to Law Number 32 of 2004 concerning Regional Government and Law Number 33 of 2004 concerning Financial Balance between the Central Government and Regional Government, the administration of regional government is carried out by granting the broadest authority. -the breadth, accompanied by the granting of rights and obligations to implement regional autonomy in the unit of the state administration system. Each head of government can manage regional income effectively and efficiently in service and contribution to the community. The aim is to analyze the contribution and effectiveness of the Regional Original Revenue (PAD) of Manggarai Regency in 2017-2019. The results of this study show that in 2017-2019 a very good level of contribution is found in the Manggarai Regency's Original Regional Revenue, namely Other Legitimate Regional Original Income, in 2017 it is 76.02%, in 2018 it is 64.99%, and in 2019 of 69.59%. The very effective level of effectiveness is Other Legitimate Local Revenue, where in 2017 it was 102.23%, in 2018 it was 113.11%, and in 2019 it was 137.57%.